Digging for the history of man. part 1 3000 B.C. - 600 A.D. (Northbrook, Ill. Roland Collection of Films in Art, 1987)
A survey of the archeological explorations in which evidence of the art and architecture of the Babylonians. Supernumeraries, Hittites, Greeks, and Romans was discovered.
VHS format.
Director / narration, H.J. Hossfeld ; original music, Enno Dugend.
Keywords: Art, Ancient -- Middle East; Art, Ancient -- Mediterranean Region; Middle East -- Antiquities; Mediterranean Region -- Antiquities